Convergent Evolution Driven by Rifampin Exacerbates the Global Burden of Drug-Resistant Staphylococcus aureus - Romain Guérillot (American Society for Microbiology, 2018)
ABSTRACT Mutations in the beta-subunit of bacterial RNA polymerase (RpoB) cause resistance to rifampin (Rifr), a critical antibiotic for treatment of multidrug-resistant Staphylococcus aureus. In vitro studies have shown that RpoB mutations confer decreased susceptibility to other antibiotics, but the clinical relevance is unknown. Here, by analyzing 7,099 S. aureus genomes, we demonstrate that the most prevalent RpoB mutations promote clinically relevant phenotypic plasticity resulting in the emergence of stable S. aureus lineages, associated with increased risk of therapeutic failure through generation of small-colony variants (SCVs) and coresistance to last-line antimicrobial agents. We found eight RpoB mutations that accounted for 93% (469/505) of the total number of Rifr mutations. The most frequently selected amino acid substitutions affecting residue 481 (H481N/Y) were associated with worldwide expansions of Rifr clones spanning decades. Recreating the H481N/Y mutations confirmed no impact on S. aureus growth, but the H481N mutation promoted the emergence of a subpopulation of stable Rifr SCVs with reduced susceptibility to vancomycin and daptomycin. Recreating the other frequent RpoB mutations showed similar impacts on resistance to these last-line agents. We found that 86% of all Rifr isolates in our global sample carried the mutations promoting cross-resistance to vancomycin and 52% to both vancomycin and daptomycin. As four of the most frequent RpoB mutations confer only low-level Rifr, equal to or below some international breakpoints, we recommend decreasing these breakpoints and reconsidering the appropriate use of rifampin to reduce the fixation and spread of these clinically deleterious mutations. IMPORTANCE Increasing antibiotic resistance in the major human pathogen Staphylococcus aureus is threatening the ability to treat patients with these infections. Recent laboratory studies suggest that mutations in the gene commonly associated with rifampin resistance may also impact susceptibility to other last-line antibiotics in S. aureus; however, the overall frequency and clinical impact of these mutations are unknown. By mining a global collection of clinical S. aureus genomes and by mutagenesis experiments, this work reveals that common rifampin-induced rpoB mutations promote phenotypic plasticity that has led to the global emergence of stable, multidrug-resistant S. aureus lineages that are associated with increased risk of therapeutic failure through coresistance to other last-line antimicrobials. We recommend decreasing susceptibility breakpoints for rifampin to allow phenotypic detection of critical rpoB mutations conferring low resistance to rifampin and reconsidering the appropriate use of rifampin to reduce the fixation and spread of these deleterious mutations globally.